PENGARUH AKUNTANSI HIJAU, KINERJA LINGKUNGAN, AKUNTANSI BIAYA ALIRAN MATERIAL TERHADAP PEMBANGUNAN BERKELANJUTAN - Kakarika; Harti Budi Yanti (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2025)
Globally, the world's attention to sustainable development has experienced a significant impact. The Primary Consumer industry sector is experiencing a significant impact, it can have positive and negative impacts, one of the negative impacts is environmental pollution. One solution to this impact is the implementation of green accounting, environmental performance and material flow cost accounting. The purpose of this study was to determine and analyze the effect of green accounting, environmental performance, material flow cost accounting on sustainable development with profitability as a control variable in primary consumer sector companies. This study uses primary consumer sector companies listed on the Indonesia Stock Exchange from 2021 - 2023. The sampling method used purposive sampling, so that the sample obtained amounted to 82 and the total data used was 130 data. The data analysis tool used is panel data regression using eview 12. The results of the study using panel data regression analysis show that: (1) Green accounting has an effect on sustainable development, (2) environmental performance has no effect on sustainable development, (3) material flow cost accounting has no effect on sustainable development.